2008
DOI: 10.1111/j.1523-1739.2008.00906.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Biodiversity Conservation around a Large Sumatran Protected Area

Abstract: Many of the large, donor-funded community-based conservation projects that seek to reduce biodiversity loss in the tropics have been unsuccessful. There is, therefore, a need for empirical evaluations to identify the driving factors and to provide evidence that supports the development of context-specific conservation projects. We used a quantitative approach to measure, post hoc, the effectiveness of a US$19 million Integrated Conservation and Development Project (ICDP) that sought to reduce biodiversity loss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
50
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 32 publications
(35 reference statements)
5
50
0
Order By: Relevance
“…It has also been suggested that REDD+ could utilise its multilevel institutional connectedness with State and global actors to address underlying drivers of deforestation (Blom et al, 2010). Such institutional strategies could correct ICDP failures, related to poor linkages with broader institutional contexts, to address underlying drivers of deforestation (Linkie et al, 2008;Kremen et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been suggested that REDD+ could utilise its multilevel institutional connectedness with State and global actors to address underlying drivers of deforestation (Blom et al, 2010). Such institutional strategies could correct ICDP failures, related to poor linkages with broader institutional contexts, to address underlying drivers of deforestation (Linkie et al, 2008;Kremen et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The second factor cited above -the myths, paradigms, or ideologies that frame human activities -has also been identified as a weakness of many conservation strategies [1][2][3][4]. Indeed, ICDPs and CBCs have emerged over the last few decades in response to the recognition that humans and protected areas must successfully coexist in order to ensure the long-term viability of conservation efforts.…”
Section: Introductionmentioning
confidence: 99%
“…The challenges and limitations facing conservation strategies such as integrated conservation and development projects (ICDPs), community-based conservation (CBC), and traditional protected areas like national parks are well documented in the literature [1][2][3][4]. These include the need for thematic coherence at the design phase, an understanding of community heterogeneity and complexity, including local communities in all phases of a project, mechanisms for monitoring and evaluation with respect to project goals and objectives, collaboration with other relevant projects, and the adoption of adaptive and flexible management approaches [1,4].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations